Teaching the root locus technique with plots categorization in an automatic control course. Issue 1 (January 2015) - Lin, Pei-Chun
The root locus is one of the major topics covered in an undergraduate-level automatic control course. It usually involves a nontrivial number of constructing steps, which on many occasions is hard for students to follow. Here, a short summary lecture taught after the normal root locus lecture is proposed. This method treats the root locus as a variation of the one or multi coefficients of the polynomials, and it categorizes various root locus plots into groups by utilizing complementary root loci and analytic or breakaway analysis. Through the combined lecture, the student learning process can be executed more smoothly and effectively.